Cultivating nutrition: a survey of viewpoints on integrating agriculture and nutrition - Levin, Carol E.; Long, Jennifer; Simler, Kenneth R.; Johnson-Welch, Charlotte (International Food Policy Research Institute, 2003)
Over the past decade, donor-funded policies and programs designed to address undernutrition in the Global South have shifted away from agriculture-based strategies toward nutrient supplementation and food fortification programs. Given the potential benefits resulting from agriculture-based nutrition interventions, this study uses Q methodology to explore the views of a range of stakeholders from both developed and developing countries on the value of—and constraints related to—gender-sensitive, nutrition-oriented agricultural projects. The three distinct viewpoints that emerge from this exercise all support the use of agricultural strategies to improve nutrition and underline the importance of gender-sensitive approaches. The viewpoints differ, however, on the relative importance of nutrition education, the strategic use of nutrient supplementation and food fortification, and the degree to which agriculture-based approaches have an impact on nutrition. The findings indicate that there is common ground among a range of stakeholders—donors, researchers, policymakers, and program practitioners—on the benefits of agriculture and gender-sensitive strategies to improve nutrition. These areas of agreement can serve as a foundation for forging an effective integrative strategy to improve nutrition that includes gender-sensitive agricultural approaches.